CEO Narcissism and CEO Overconfidence on Firm Performance: The Role of Capital Structure as Mediating Variable - Candy, Candy; Delfina, Delfina (University of Merdeka Malang, 2023)
Chief Executive Officers (CEO) have an important role in a company’s future, including the financial decisions of a company. Therefore, this study investigates the role of capital structure as a variable that mediates the effect of CEO narcissism and CEO overconfidence towards the performance of Indonesian infrastructure companies that are listed on the Indonesia Stock Exchange. This study obtained 39 companies as a study sample from 2017 to 2021 and analyzed them using the multiple linear regression method. This study found that capital structure is negatively affected by CEO narcissism, and positively affected by CEO overconfidence. Capital structure doesn’t affect Return on Asset (ROA) but negatively affects Return on Equity (ROE). CEO narcissism doesn’t affect firm performance as measured by ROA but positively affects ROE. Unlike the CEO overconfidence doesn’t affect either ROA or ROE. Moreover, the capital structure can mediate the impact of CEO narcissism and overconfidence on ROE, but it cannot mediate the impact on ROA. The results of this study contribute to academics as well as corporate knowledge as research regarding CEO narcissism and CEO overconfidence is uncommon and can be useful as a reference for companies.